2000
DOI: 10.1159/000007732
|View full text |Cite
|
Sign up to set email alerts
|

40- to 100-kD Protein(s) of <i>Helicobacter pylori</i> Stimulate DNA Synthesis in Epithelial Cell Lines without Affecting Apoptosis

Abstract: Background: Previous in vitro studies have demonstrated that water extracts and sonicates of Helicobacter pylori increase DNA synthesis in a small intestinal epithelial cell line. The aim of this study was to identify mitogenic factor(s) in a water extract of a H. pylori strain and to examine their effects on DNA synthesis and apoptosis in vitro. Methods: IEC-6 and FHs 74 cells were incubated for 24 h with different dilutions of a water extract of H. pylori (cytotoxic strain 88–23) or with 6 protein fractions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2001
2001
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
0
1
Order By: Relevance
“…There have been several reports that water extracts of H. pylori stimulate DNA synthesis in rat small intestinal IEC-6 cells. [19][20][21] However, Kurosawa et al 22 reported that water extracts of H. pylori inhibited cell proliferation of human umbilical vein epithelial cells with decreased labeling index of BrdU. The cause for the difference in the effect of the water extract on DNA synthesis is unclear, but it is possible that the difference in H. pylori strains, cell lines, and methods of quantifying DNA synthesis might account for the discrepancy in the results between previous reports and the present study.…”
Section: Discussioncontrasting
confidence: 72%
“…There have been several reports that water extracts of H. pylori stimulate DNA synthesis in rat small intestinal IEC-6 cells. [19][20][21] However, Kurosawa et al 22 reported that water extracts of H. pylori inhibited cell proliferation of human umbilical vein epithelial cells with decreased labeling index of BrdU. The cause for the difference in the effect of the water extract on DNA synthesis is unclear, but it is possible that the difference in H. pylori strains, cell lines, and methods of quantifying DNA synthesis might account for the discrepancy in the results between previous reports and the present study.…”
Section: Discussioncontrasting
confidence: 72%